Psychological factors influencing pro-environmental attitudes in children - Emilija Marković; Slađana Vidosavlјević; Jelena Krulј; Nataša Lazović (University of Banja Luka, Faculty of physical education and sport, 2022)
One of the main requirements of modern society, and for the sake of its survival, is the formation of socially responsible behavior towards the greatly endangered environment. Every day we are faced with the problems of pollution, global warming, depletion of the ozone layer and many others. Therefore, it is of paramount importance to influence the youngest generations to develop attitudes that will develop a high awareness of the need to protect nature and how to treat it. In this sense, today, and for the sake of the future, we must actively work on the development of pro-environmental attitudes in children, which would manifest themselves in pro-environmental behavior tomorrow. The development of this cognitive component, that is, the attitude requires the society to instil in the child knowledge about nature, its benefits, but also its demands and the inseparability of man from it, which affects the child's affective relationship towards it, the feeling of attachment to the environment that becomes an integral part of values. With their conative component, attitudes also initiate individuals to act. This especially necessary during the current COVID-19 pandemic and the unresolved question of the origin of the virus. Was it created artificially in laboratories or is it of natural origin, as nature's response to man's relationship to it. Some studies show that children in the first grades of elementary school understand the phenomenon of environmental pollution, they even know about different types of pollution, but they still do not understand the causes of these events. Therefore, although there is not much research dealing with this problem, we consider it important to analyse current knowledge about the psychological factors influencing the development of pro-environmental attitudes in children. pro-environmental attitudes, pro-environmental behaviour, identification, self-efficacy